2011
DOI: 10.1212/wnl.0b013e3182143577
|View full text |Cite
|
Sign up to set email alerts
|

Interferon β-1b and glatiramer acetate effects on permanent black hole evolution

Abstract: Objective:To compare interferon ␤-1b (IFN␤-1b) and glatiramer acetate (GA) on new lesion (NL) (gadolinium-enhancing, new T2) evolution into permanent black holes (PBH)-a marker of irreversible tissue damage-in patients with relapsing-remitting multiple sclerosis (RRMS).Methods: BEYOND was a large, phase III, clinical trial comparing IFN␤-1b 250 g, IFN␤-1b 500 g, and GA (2:2:1). Patient scans were reexamined post hoc for PBH in a rater-blinded manner. Two predefined coprimary endpoints compared IFN␤-1b 250 g wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 24 publications
1
24
1
Order By: Relevance
“…The evolution of active lesions into PBH was assessed as previously described 14 21. New lesions were defined as a GdE lesion and/or a new T2 lesion arising from an area of previously normal-appearing WM.…”
Section: Methodsmentioning
confidence: 99%
“…The evolution of active lesions into PBH was assessed as previously described 14 21. New lesions were defined as a GdE lesion and/or a new T2 lesion arising from an area of previously normal-appearing WM.…”
Section: Methodsmentioning
confidence: 99%
“…However, the effects are transient and repeated treatments with high-dose steroids have too many complications to be used routinely. A more sustained reduction of BBB damage occurs with immunomodulatory drugs, such as interferon-b and glatiramer acetate (Filippi et al, 2011;Kala et al, 2011).…”
Section: Treatment In Blood-brain Barrier Disruption and Future Direcmentioning
confidence: 99%
“…170,226,[229][230][231] Of these 27 trials, one evaluated HRQoL measures alone 181 and one evaluated AEs alone. 182 In addition, two trials reported on mixed populations.…”
Section: Summary: Clinically Isolated Syndromementioning
confidence: 99%